Analysis of Hygiene and Sanitation Implementation in the Pastry Division at Aruss Hotel Semarang - Grace Marveline Lucky Hantiono; U. Yuyun Triastuti (An International Journal Tourism and Community Review, 2026)
The hospitality industry is a strategic sector within the global tourism system that heavily depends on service quality and food safety assurance. In hotel operations, the pastry division represents a high-risk unit due to the use of perishable ingredients and intensive manual handling processes. This study aims to analyze the implementation of hygiene and sanitation practices in the Pastry Division of Hotel Aruss Semarang in supporting food safety standards within the hospitality industry. This research employs a qualitative approach with a case study design. Data were collected through participatory observation, semi-structured interviews, and document analysis, including Standard Operating Procedures (SOPs), sanitation checklists, and temperature control records. Data validity was strengthened through triangulation and member checking, while thematic analysis was used to identify key implementation patterns. The findings indicate that the implementation of personal hygiene, environmental sanitation, and Good Manufacturing Practices (GMP) has generally complied with most of the requirements of Good Processed Food Manufacturing Practices (CPPOB). The availability of sanitation facilities, periodic medical check-ups, equipment maintenance, and FIFO-based storage systems demonstrate management commitment to preventive risk control. However, inconsistencies in handwashing practices and minor construction details that do not fully meet hygienic design standards indicate areas requiring improvement. Overall, hygiene and sanitation implementation in the Pastry Division has been effective in supporting food safety. Strengthening behavioral compliance, continuous training, and facility optimization are recommended to achieve a more sustainable and comprehensive food safety management system.